Unravelling ties in the nitrogen network: Polyamines and nitric oxide emerging as essential players in signalling roadway - Recalde, Laura (2020)
Nitrogen (N) is a central mineral nutrient essential for plant development and growth. It is usually scarcely found in soils, so the knowledge of the overall plant N metabolism deserves substantial attention. Polyamines (PAs) are N-containing low-molecular-weight compounds of polycationic nature involved in essential processes all throughout the life of plants whereas nitric oxide (NO) is a gaseous free radical involved in signalling cascades related to many physiological events. PAs and NO share signalling functions and interact with each other in several biological functions, mainly in stress responses. Biosynthesis pathways of PAs and NO are overlapped; PAs induce NO formation, but it is still not completely defined whether PAs act as substrates, cofactors, or signals for promoting NO synthesis and also, which are the mechanisms involved in NO regulation of PAs metabolism. Polyamine levels are of vital importance in the regulation of the network of N-metabolising pathways in plants, as they are components of the core of the overall N metabolism. In light of the importance of improving the efficiency of N uptake and distribution, it is time to elucidate the intricate relationship among N as a nutrient with PAs and NO as emerging signalling molecules. The close cooperation among these players in the whole N metabolism is an interesting target for the development of biotechnological tools for sustainable agriculture.